The Prevalence of Anemia in Elderly With Systolic Heart Failure - Sharareh Zeighami Mohammadi; Soolmaz Asgharzadeh Haghighi; Neda Falah (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: Anemia is prevalent in heart failures and is an independent risk factor for adverse clinical outcomes in patients with CHF. The aim of the present study was to determine the prevalence of anemia in elderly with systolic heart failure hospitalized in Alborz Hospital of Karaj in 2009. Methods & Materials: This is a descriptive retrospective study that reviewed 154 medical records of elderly with systolic heart failure during 2002-2008. Demographic, laboratory, and echocardiography data were reviewed from medical records. Anemia was defined as a hemoglobin level below 12 g/dL in women and below 13 g/dL in men in this study. Data were analysed by descriptive statistics such as frequency distribution, mean, standard deviation and independent group test and Pearson correlation coefficient. Results: The findings indicated that prevalence of anemia in elderly with systolic heart failure was (42.9%). There was significant difference between mean level of hemoglobin in heart failure with chronic obstructive pulmonary disease (P=0.000). level of hemoglobin significant associated with age (P=0.014) and left ventricular ejection fraction (0.022). Conclusion: This study indicated that anemia is frequent among elderly with systolic heart failure and anemia may be associated with age, LVEF and COPD. More research into the mechanisms of anemia in CHF is needed.